The electroreduction of benzoic acid: voltammetric observation of adsorbed hydrogen at a platinum microelectrode in room temperature ionic liquids. - Meng, Y; Norman, S; Hardacre, C; Compton, R (2013)
The electrochemical reduction of benzoic acid in the presence and absence of hydrogen (H(2)) has been investigated using a 10 μm diameter platinum microelectrode in four different room temperature ionic liquids (RTILs), namely [C(4)mim][NTf(2)], [C(4)mpyrr][NTf(2)], [C(4)mim][OTf] and [C(4)mim][BF(4)], versus Ag/Ag(+). In all cases, reductive voltammetry is observed, and is suggested to occur via a CE mechanism in which dissociation of benzoic acid is followed by electron transfer to H(+) ultimately forming adsorbed hydrogen. Furthermore, the adsorbed H atoms, formed from the reduction of benzoic acid, could be used to achieve the rapid hydrogenolysis of the organic compound (bis(benzyloxycarbonyl)-l-lysine) on the timescale of the voltammetric technique under moderate conditions (25 °C).